Breeding practices of indigenous chickens in the Liban Jawi District of the West Shewa Zone, Ethiopia: A qualitative and quantitative analysis - Desalegn Begna; Teferi Bacha; Shambel Boki; Kasahun Bekana (Poultry Science)
A study was conducted in 2022 in the Liban Jawi district to characterize the breeding practices of indigenous chickens. A total of 192 farmers were surveyed, revealing diverse breeding objectives, including income generation, egg consumption, savings, and meat consumption. Limited selective breeding was observed, with plumage color, egg number, broodiness, hatchability, and male body weight as common selection traits. Most farmers practiced uncontrolled natural mating and were unaware of the risks of inbreeding. Culling underproductive chickens, undesirable colored cockerels, or pullets at an early age, along with selling or slaughtering, were employed to prevent unwanted mating. Correspondence Analysis (CA) revealed significant relationships among phenotypic traits, with Dimension 1 accounting for 39.43 % of total inertia, indicating that environmental conditions heavily influence trait selection. The Chi-Squared Distance analysis highlighted strong preferences for Egg Number (D = 15.23) and Hatchability (D = 12.45), both showing highly significant P-values (p = 0.001 and p = 0.002 respectively). Additionally, farmers expressed significant preferences for Disease Resistance (D = 11.56, p = 0.003) and Body Size (D = 10.12, p = 0.012). This research provides valuable insights into the breeding practices of indigenous chickens in the unique context of the Liban Jawi District, Ethiopia. By combining qualitative and quantitative analyses, the study emphasizes the significance of indigenous knowledge, identifies challenges, and underscores the implications for sustainable rural livelihoods. The findings advocate for effective trait selection and the implementation of controlled mating systems to mitigate inbreeding risks and enhance productivity in indigenous chicken populations.